Nauczycielki Ziemi Wileńskiej w latach 1915–1923 - Falkowska, Joanna (Biuletyn Historii Wychowania, 2020)
During the political changes in Vilnius County, i.e. in the territory of the Second Polish Republic (1922–1926) with the capital in Vilnius, after 1914 the Polish society hoped for full acceptance of educational institutions, operating illegally before the outbreak of WWI. Despite significant difficulties created by the German occupier, Polish education – both general and secondary – was organized. It was mean feat primarily due to the lack of teachers. In the early 20th century, two schools preparing for the teaching profession operated in Vilnius: the Nazareth Sisters and an institution organized by Agata Karpowiczówna. Recognizing the need to educate teachers, a school for women named after Queen Jadwiga was founded in 1916, and soon afterwards the Education Committee established five more schools. Meanwhile, junior and senior high schools were also established in Vilnius. On the basis of archival research carried out by the authors of the article in the Lithuanian State Historical Archive in Vilnius, numerous applications and biographies of candidates for educators, primarily in the Vilnius area, were collected and presented. This documentation is diverse as it consists of surveys regarding personal data and the course of work, applications handwritten by the candidates, opinions of former superiors but also correspondence on the basis of which. the candidate’s studies and work can be reconstructed. The above-mentioned documentation comes from 1919–1923 i.e. a period of slow stabilization of education in the area in question.